2021
DOI: 10.51601/ijersc.v2i1.42
|View full text |Cite
|
Sign up to set email alerts
|

Effect Technology Information On Quality Financial Statement With Internal Control As Moderating Variable

Abstract: The problem with the low quality of financial reports in local governments is the reason this research was conducted. This research was conducted with the aim of analyzing the use of information technology on the quality of financial reports by considering the internal control system (SPI) factor. The location of this research is in the Karisidenan Surakarta area which includes 6 districts and 1 city. The population of this research is all state civil servants (ASN) in local governm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…al., 2021). The findings in this study strengthen and validate statements from research by Sarwono and Handayani (2021) which explain that system-based information technology can produce quality information in decision making. There is an internal control system with the implementation of the ERP system in accordance with the components of internal control according to COSO (1992); control environment, risk assessment, control activities, information and communication, and monitoring carried out by management and company employees in accordance with policies that have been made, so that company goals can be achieved and produce quality financial reports.…”
Section: Discussionsupporting
confidence: 83%
“…al., 2021). The findings in this study strengthen and validate statements from research by Sarwono and Handayani (2021) which explain that system-based information technology can produce quality information in decision making. There is an internal control system with the implementation of the ERP system in accordance with the components of internal control according to COSO (1992); control environment, risk assessment, control activities, information and communication, and monitoring carried out by management and company employees in accordance with policies that have been made, so that company goals can be achieved and produce quality financial reports.…”
Section: Discussionsupporting
confidence: 83%
“…The value of the Current ratio in a high industry means that the industry will increase the profit for investors. In other words, this current ratio compares the amount of available short-term assets owned by the sector and total current liabilities [45]. well, the value of the current ratio will be directly proportional to the high ability of an industry to pay off its short-term financial obligations.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Marlizar et al, (2021) argued that the use of IT by users to carry out deployment is based on utilization intensity, frequency of use and number of applications or software. Choeroh et al, (2023); Indriyani & Mappanyukki (2022); Sarwono & Handayani (2021); Ulisanti & Asrori (2021); Aswar (2020); Adnin & Atiningsih (2020); Basudewa & Putri (2020); Nadir & Hayim (2017) explained that IT affected the QLGFR. This is in line with research done by Primayana (2014); Husna (2017);and Aswar (2020), which stated that the use of IT could enhance the quality and reliability of financial reporting.…”
Section: Introductionmentioning
confidence: 99%
“…The research was conducted in 90 local government organisations in Maluku Province and each sample was represented by one respondent. Sarwono & Handayani (2021) showed that the use of IT has a positive effect on the QLGFR in the region of Surakarata which included 6 regencies and 1 City government. The population of the research cover all the local civil servant who worked in the field of accounting.…”
Section: Introductionmentioning
confidence: 99%